Adaptation of sheep breeding systems to changes in the Algerian steppe context: Case of the region of M’Sila - Hadbaoui I.; Senoussi A.; Huguenin J. (Innovation for sustainability in sheep and goats, 2019)
The Algerian steppe extends over an area of 20 million hectares (rainfall between 100 and 400 mm/year). It supports a grazed ecosystem whose balance had been found by local populations, in particular through movements of animals (Achaba and Azzaba). But for about half a century, the steppe knew many socio-economic and environmental changes, of which the most notable: (i) the depletion of naturals pastures, as a result of the degradation of the steppe rangelands, (ii) an accelerated demographic growth, which is reflected in an increase in household needs and the necessity to find a satisfactory income for the family, and (iii) economic instability, especially the arrival of imported livestock feed. And despite the upheaval which the steppe knew, the breeders still keep the activity of sheep breeding and herd numbers are constantly increasing. Hence the need for making studies to understandthe dynamics of the breeding systems, very important element in the implementation of development programs. In this study, we are interested in the analysis of the different mechanisms of flexibility and adaptation of sheep breeding in M’Sila region, One of the main wilayas (departments) of the Algerian steppe. We conducted interviews with thirty sheep breeders representing the different breeding systems in the area. After analyzing the results of the undertaken interviews, we noted a wide range of practices of innovations adopted by the breeders facing to the various changes in the socioeconomic and environmental contexts, both nationally and locally. Diversification of sources of income, readjustment of tribal rangelands distribution rules, adaptation of animal feeding to the fodder deficit, are all indications that the present study attempts to clarify.
2. Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2017/10/03-05, Vitoria-Gasteiz (Spain)